1993
DOI: 10.1128/mcb.13.1.473
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic commitment during embryonic stem cell differentiation in culture.

Abstract: We report that embryonic stem cells efficiently undergo differentiation in vitro to mesoderm and hematopoietic cells and that this in vitro system recapitulates days 6.5 to 7.5 of mouse hematopoietic development. Embryonic stem cells differentiated as embryoid bodies (EBs) develop erythroid precursors by day 4 of differentiation, and by day 6, more than 85% of EBs contain such cells. A comparative reverse transcriptase-mediated polymerase chain reaction proffle of marker genes for primitive endoderm (collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
632
3
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 847 publications
(671 citation statements)
references
References 68 publications
35
632
3
1
Order By: Relevance
“…We observed mRNA within 2-3 days for nestin (an early neural ectoderm marker) and brachyury (Brachy, an early mesoderm marker), whereas ÎČ-H1 globin (ÎČ-globin, a mesoderm marker) and α-fetoprotein (α-FP, an endoderm marker) mRNAs accumulated later (days 5-6). These patterns of expression are as previously reported for multilineage differentiation following LIF withdrawal [8,9,32,[38][39][40][41].…”
Section: Progesterone Receptor Gene Is Expressed Early During Differesupporting
confidence: 88%
See 1 more Smart Citation
“…We observed mRNA within 2-3 days for nestin (an early neural ectoderm marker) and brachyury (Brachy, an early mesoderm marker), whereas ÎČ-H1 globin (ÎČ-globin, a mesoderm marker) and α-fetoprotein (α-FP, an endoderm marker) mRNAs accumulated later (days 5-6). These patterns of expression are as previously reported for multilineage differentiation following LIF withdrawal [8,9,32,[38][39][40][41].…”
Section: Progesterone Receptor Gene Is Expressed Early During Differesupporting
confidence: 88%
“…CCE mES cells were used for all studies except where indicated and were obtained from Dr. John Gearhart (Johns Hopkins University) with permission from Dr. Gordon Keller [31,32]. Plastic tissue culture dishes were pretreated with 0.1% porcine gelatin Type A (Sigma) in water for 30 min to 2 hrs at 37ÂșC.…”
Section: Cell Culturementioning
confidence: 99%
“…Embryoid body-mediated differentiation to generate macrophages from mouse ES cells has been reported by several groups [31][32][33][34]. In the present study, we demonstrated efficient generation of functional macrophages from mouse iPS cells.…”
Section: Discussionsupporting
confidence: 73%
“…Receptor numbers subsequently decrease as terminal differentiation proceeds. While erythropoietin transcripts have been detected in the mouse embryo at E7.5 and in the fetal liver at E14.5, the low levels of erythropoietin expression have hampered the spatial and temporal analysis of its expression during development [36][37][38]. A small percentage (7%-10%) of a supraphysiologic dose of erythropoietin can cross the mouse placenta just prior to birth (E19) [39].…”
Section: Primitive Erythropoiesis Originates In the Yolk Sacmentioning
confidence: 99%